Rhythms for Living: Fluid Cultural Adaptations within the Dynamic Watersheds of Eastern Indonesia - Fowler, Cynthia Twyford; Konradus, Blajan; Widinugraheni, Sri; Dasion, Agustinus Gergorius Raja (Forest and Society, 2025)
Tectonics literally and figuratively create rhythms for living in the seismically active nation of Indonesia where shifting plates generate landforms around which cultures construct their homelands. Eastern Indonesian communities who have built their societies around the region’s dynamic watersheds have constructed traditional ecological knowledge and place-based skills for accessing freshwater. What is the water-related knowledge and skills of Indigenous societies who live in the tropical monsoon climate zone of Nusa Tenggara Timur Province (NTT)? How have communities living on Sumba Island in southern NTT adapted to their homelands where they find water to pose the most difficult challenge to survival? How do Sumbanese continue adapting to ongoing natural and anthropogenic changes in their island’s hydrological systems? Ecological rhythms inform cultural constructions of freshwater ecosystems and the ways people manage water. Despite the dynamism of tectonic and oceanic-atmospheric processes, they are steadier in some ways than misguided anthropogenic developments. We describe changes that have occurred over the past quarter century in the ways Sumbanese interact with and manage freshwater following the premise that socioeconomic transformations coincide with changes in freshwater ecology. We focus on the culturally specific management of water within the North Kodi Subdistrict of the South West Sumba Regency and the hydrological setting of residents’ lives. To understand the latter, we reviewed scientific literature and to study the former we conducted ethnographic fieldwork. Our findings show the impacts of hydrological developments on communities reflect existing social structures. In stratified societies, development has uneven impacts. Our research reveals anthropogenic change to be nonlinear. While people may adjust their water-related practices to novel developments, they also may revert to historically proven behaviors when developments fail. Resilience is an inherent quality of cultural adaptations to hydrological systems in the dry tropical biomes of Indonesia.